Binational Heraeus Summer School: Astronomy from 4 perspectives: IV – Origins of stars and planets - , (Il Colle di Galileo, 2017)
The Heraeus Summer Schools “Astronomy from four perspectives” bring together teachers, professional astronomers, student teachers and university astronomy students from Germany and Italy. Each Summer School has a different astrophysical theme. After Heidelberg 2013, Padua 2014 and Jena 2015, the fourth edition took place in Florence in August 2016. The aim is to create and maintain a network of university and high school teachers and to develop materials and methods on current research in astronomy and astrophysics to be used in high schools.